1983
DOI: 10.1016/s0022-5347(17)52131-x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Phagocytic function of Urinary Leukocytes

Abstract: Urine specimens from patients with urinary tract infection (UTI) were examined to determine the rate of phagocytosis and viability of urinary leukocytes. The phagocytic function of urinary leukocytes was also studied in vitro. The mean rate of viable urinary leukocytes was 83 per cent and the phagocytic potency was confirmed by light and electron microscopic studies. In 99 per cent of 113 patients with UTI, urinary leukocytes were shown to have phagocytized bacteria. The rate of phagocytosis in chronic UTI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…Our observations of effective phagocytosis in urine at both 200 and 485 mosM agree with the results of others (20,24). Suzuki and colleagues showed that there was only a onethird loss in phagocytic activity when PMN exposed to urine with an osmolality of less than 200 or greater than 550 mosM were removed from the urine for phagocytosis studies (25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observations of effective phagocytosis in urine at both 200 and 485 mosM agree with the results of others (20,24). Suzuki and colleagues showed that there was only a onethird loss in phagocytic activity when PMN exposed to urine with an osmolality of less than 200 or greater than 550 mosM were removed from the urine for phagocytosis studies (25).…”
Section: Discussionsupporting
confidence: 91%
“…This supports the observations of Cox and Hinman on the antibacterial activity of the bladder wall (7). Other workers have reported that PMN contribute to the defense of the bladder in experimental infections (15) and that PMN in the urine of patients with urinary tract infections contain phagocytosed bacteria (20); these reports do not establish whether the phagocytosis observed takes place in or at the surface of the bladder wall or in the urine.…”
supporting
confidence: 65%
“…Stadler et al (34) and Gillon et al (11) have histologically indicated that PMN, together with locally produced opsonizing and agglutinating antibodies, participate in bacterial clearance from the bladder in P. mirabilis and E. coli UTI models using mice undergoing water-diuresis. Maeda et al (20) have shown by careful lightand electron-microscopic examinations of urine specimens from patients with UTI that PMN actually phagocytize bacteria with a high frequency. All these authors have concluded that the phagocytic activity of PMN constitutes a crucial defense mechanism in the bladder against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, some early studies documented that since the phagocytic function of PMN was suppressed in the urine by its extremes of osmolarity, pH, and urea concentration, PMN might not play an important role in the pathogenesis of UTI (6,7,23). Conversely, subsequent histological studies on experimental UTI models have found that bacteria that penetrated into the submucosa of the bladder wall were often phagocytosed by PMN drained through the lymphatics or veins, and have suggested that phagocytic killing by PMN does play an important role in the defense of the bladder against bacterial infection (8,11,20,26,34). Some analytical studies on the initial stages of host-parasite interaction in an experimental UTI mouse model with E. coli have also indicated that the accumulation of inflammatory cells in the kidneys and bladder tissue is a major defense mechanism against E. coli in the urinary tract (12,13,31,37).…”
mentioning
confidence: 99%
“…It is becoming clear that in addition to facilitating the initiation of bacterial infections, adhesive fimbriae expressed by different pathogenic bacteria may modulate survival in the host by modifying the interaction of bacteria with various inflammatory cells, including neutrophils (30,39). Histological examination of kidney and bladder tissue in experimental monkey and mouse models indicates that accumulation of neutrophils in the kidney and bladder tissue is a major host defense mechanism against E. coli-induced UTI (13,24,28,38). The fact that large numbers of neutrophils are often found in the urine of patients with UTI is another indication of the active involvement of neutrophils in host defense in the urinary tract.…”
mentioning
confidence: 99%